Roles of recycled oils, polyphosphoric acid and sulfur on chemo-rheological and morphological properties of high-viscosity modified asphalt. (31st March 2023) - Zhang, Jinxi; Yang, Duowang; Sun, Guoqiang; Li, Yiwen; Qi, Yue; Ma, Xiaoyan
Graphical abstract: Highlights: It is studied if recycled oils can replace aromatic oil as compatibilizer of HVMA. Recycled oils show greater rheological improvement on HVMA than aromatic oil. Synergistic effect of PPA and sulfur have excellent modification role on HVMA. Adding recycled oils alone does not improve storage stability of HVMA. Combination of REO and chemical stabilizers greatly improves storage stability of HVMA. Abstract: Using recycled oils and chemical stabilizers as the additives in high-viscosity modified asphalt (HVMA) is being developed as a sustainable way to solve the severe segregation problems due to the large differences in nature between high-content styrene–butadienestyrene (SBS) and base asphalt. This paper attempts to use three recycled oils, namely castor oil (CO), waste cooking oil (WCO) and recycled engine oil (REO), as compatibilizers in combination with different chemical stabilizers (polyphosphoric acid, PPA; sulfur) to investigate their ameliorative roles on HVMA segregation problems. By means of the gel permeation chromatography, dynamic shear rheometer and fluorescence microscopy, the chemo-rheological properties and morphological structures of HVMA are investigated, as well as their storage stability. Results show that the recycled oils are more favorable to improve the high-temperature rheological performance of HVMA than aromatic oil (AO) by comprehensively considering the softening point, zero-shear viscosity, elastic recovery percent and large molecule percentage, and the role ranking is: REO > WCO > CO > AO. Compared with the addition of PPA or sulfur alone, when PPA and sulfur are added together, the rheological performance of HVMA is promoted most significantly, because of the synergistic cross-linking reaction of these chemical stabilizers with asphalt and polymers. Furthermore, the synergistic effect of PPA and sulfur markedly reduces the temperature sensitivity of HVMA. However, the cigar tube test reflects that adding recycled oils as compatibilizers alone can not improve the storage stability of HVMA, and CO and WCO even aggravate its segregation. Notably, adding REO and chemical stabilizers can markedly improve the storage stability of HVMA, and the effect is most obvious when REO, PPA and sulfur are added together.